Perancangan Sistem Pencatat Kecepatan Angin Untuk Studi Kelayakan Pembangunan Pembangkit Listrik Tenaga Bayu (Pltb) Berbasis Internet Of Things (Iot) - Husada, Rahmadi; Joni Eka Candra; Luki Hernando; Masril, M Abrar (LPPM-ITEBA, 2025)
Wind is one of the potential renewable energy sources that is gaining increasing attention in efforts to diversify energy resources. This study aims to design and implement a wind speed recording system based on the Internet of Things (IoT) to facilitate feasibility studies for wind energy utilization. The system uses an Anemometer sensor to measure wind speed, a NodeMCU ESP8266 as the microcontroller, and a 20x4 I2C LCD to display data in real-time. The generated data will be transmitted wirelessly via a Wi-Fi network to the Arduino IoT Cloud platform, where it can be accessed and analyzed remotely. The main challenge in designing the wind speed recording system is integrating various hardware and software components to ensure system interoperability and optimal performance. To address this issue, a modular approach was taken using standard interfaces and phased integration testing. Furthermore, the wind speed recording system was tested in two highland areas and two coastal areas, all of which are open areas, namely Bukit Tiban Ayu, Bukit Tangga Seribu, Pantai Cipta Land located in Sekupang District, and the second Barelang Bridge. The measurements yielded average wind speed recordings of approximately 0.60 m/s at Bukit Tiban Ayu and Pantai Cipta Land, around 0.88 m/s at Bukit Tangga Seribu, and 1.02 m/s at the second Barelang Bridge. The measurement results at these four locations did not meet the wind energy utilization standards. The data generated from this study can be used by (wind power plant) developers as an analysis in determining the feasibility of locations for development.